Blockchain technology for crop insurance - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Creating a design for a blockchain based crop insurance. From the perspective of a smart contract, the insurance company and farmer will enter into an agreement where the service provider and weather data provider will act as Trusted Third Parties providing information on the triggers for executing the contract.